2013
DOI: 10.1158/1541-7786.mcr-13-0212
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of PI3K and mTOR Mitigates Compensatory AKT Activation and Improves Tamoxifen Response in Breast Cancer

Abstract: Everolimus, an mTOR inhibitor, showed great clinical efficacy in combination with tamoxifen, letrozole, or exemestane for the treatment of estrogen receptor-positive (ER+) breast cancer. However, its antitumor activity was shown to be compromised by a compensatory process involving AKT activation. Here, it was determined whether combining an additional PI3K inhibitor can reverse this phenomenon and improve treatment efficacy. In breast cancer cells

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…It has been shown that although RAD001 inhibited mTOR downstream activity, it induces p-AKT (Ser473) activation in breast cancer cells. The addition of LY294002 to RAD001 improved the anti-tumor effects and decreased p-AKT (Ser473) activity [31]. The same as this feedback mechanism in our study, RAD001 treatment resulted in AKT activation at 6 h in Calu-1 cell line.…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that although RAD001 inhibited mTOR downstream activity, it induces p-AKT (Ser473) activation in breast cancer cells. The addition of LY294002 to RAD001 improved the anti-tumor effects and decreased p-AKT (Ser473) activity [31]. The same as this feedback mechanism in our study, RAD001 treatment resulted in AKT activation at 6 h in Calu-1 cell line.…”
Section: Discussionsupporting
confidence: 77%
“…EMT is related to cancer metastasis and IL-6 has been reported to induce EMT by activating JAK-STAT3-SNAIL pathway. 12 In our work, we found that CAFs, through IL-6-mediated activation of both JAK/STAT3 and PI3K/AKT pathways, promoted EMT in MCF7 and T47D cells. These findings suggest that IL-6 from the tumor microenvironment has a critical role in inducing progression of luminal BrCA.…”
Section: Discussionmentioning
confidence: 48%
“…12 Here, we found that the invasive ability of MCF7 and T47D cells was markedly increased when cultured with CAF-CM, but was markedly inhibited by knockdown of IL-6 expression in the CAF (Supplementary Figure 4). These results suggest that secretion of IL-6 by CAFs promotes luminal BrCA invasion.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, they also disrupt a feedback mechanism that dampens PI3K activity, leading to a compensatory upregulation of Akt activity, causing counterproductive prosurvival effects. On the contrary, the ATP-competitive dual PI3K/mTORC1/2 and mTORC1/2 inhibitors display potent anticancer properties both in vitro and in vivo in a wide range of malignancies, including leukemia (9, 10). Several of these compounds are being tested in preclinical models and they show a consistently robust effect against tumors driven by PI3K/Akt signaling, while they are ineffective against tumors driven by mutations of Ras, which can signal through multiple pathways, such as those for MEK and ERK (11).…”
Section: Introductionmentioning
confidence: 99%